Mirroring the society, mirroring its hospitals: Hyginus Ekwazi’s poetry and the challenge of nation-building - Awuzie, Solomon (English Studies at NBU, 2019)
Anglophone African poetry has become a significant medium through which African society from the year 2000 to date is mirrored. The younger Anglophone African poets, widely referred to as the poets of the third-generation, have always used their poetry as means to respond to both historical and current socio-political circumstances that tend to distinguish Africa from the rest of the world. Their poetry now constitutes counter-hegemonic discourse against bad leadership in Africa and against corrupt African social and medical institutions. Using Hyginus Ekwuaziâ€™s The Monkeyâ€™s Eyes as a representative poetry of the younger Anglophone African poets, emphasis is made on how the poet depicts the African society and its hospitals. The paper analyzes the collection as a sequel to all other collections of poetry produced by the younger poets at this period. It reveals the condition in which the poetry is produced and how it has responded to the decay in African society and its hospitals. The paper points out that though the older generation of the Anglophone African poets responded to similar socio-political situation, the younger generation of the Anglophone African poets has become the prominent voice in this period and that their poetry provides a clear picture of what is happening in Africa within this time space. Being a new set of voices on the terrain of the Anglophone African poetry, a study of this poetry opens up a new platform upon which this so-called â€œaesthetic of rageâ€ is appreciated. Note: An earlier version of this paper was presented at Birkbeck University of London in an International Conference captioned â€œMirror, Mirror: Perceptions, Deceptions, Reflections in Timeâ€ organized by London Centre for Interdisciplinary Research (LCIR) on 10th March, 2018 in London, UK.